Computer security incident response planning at nuclear facilities. (International Atomic Energy Agency, 2016)
"The purpose of this publication is to assist Member States in developing comprehensive contingency plans for computer security incidents with the potential to impact nuclear security and/or nuclear safety. It provides an outline and recommendations for establishing a computer security incident response capability as part of a computer security programme, and considers the roles and responsibilities of the system owner, operator, competent authority, and national technical authority in responding to a computer security incident with possible nuclear security repercussions."--Publisher's description.